Aerial Photo of Dewey County, OK, USA, CTX-2B-54 - (:unkn) unknown (United States Government, 1941)
Oklahoma aerial photographs in this collection are public domain and were created by U.S. government agencies or contractors to those agencies. The photos are marked with a flight and frame number at the top of the photos, e.g., AQS-219. The date of the flight is then printed in the opposite corner. More information about these photos can be found at: http://guides.ou.edu/aerial. Digital imaging courtesy of the University of Oklahoma Libraries, Government Documents Collection.
Black and white photography of Dewey County, OK, USA